Effect of humic acid (HA) in some physiological characteristics and fruit quality of Plum Varieties (Prunus salicina L.) (Journal of Hama University, 2019)
Used the Humic Acid (HA) at three concentrations (1, 2, 3, ml/L) for foliar and (50,100,150 ml/L) for soil fertilization Times of fertilizations: '' stage bud-break, after fruit set, month before fruit harvest” during seasons 2017 to improve some physiological characters of two varieties of plum Beauty and Santa Rosa. The Humic Acid treatment led to improvement vegetative growth two varieties comparing with the control. That the best treatment was which had the fertilization adding by HA in concentration of (2 , 150 ml/L), which reached leaf area at Beauty variety to (450.7 cm2) in the foliar spray and (420 cm2) in the soil fertilization comparing with the control (353.4 cm2(. The HA treatment led to improvement in chemical character of fruit both varieties, increase T.S.S % at treatment HA (150 ml/L) reached to (12.25-12.11 %( comparing with the control (7.31-5.13%( to both varieties. Beauty and Santa Rosa. The treatments led to improvement content of fruit from T.S % and vitamin C. Foliar fertilization had superiority on soil fertilization in the content of leaf from total chlorophyll and percentage of dry mater, and increased of elements in the fruit mature. That reached of total chlorophyll at treatment HA(150ml/L) for Beauty (2.25mg/g (and (2.19 mg/g( for Santa Rosa with the control (1.48-1.33mg/g(  to both varieties